THE EFFECT OF PRENATAL EXERCISE ON THE INCIDENCE OF POST PARTUM DEPRESSION - Dyah Krisnawati Satia Pratiwi (Journal of Psychiatry Psychology and Behavioral Research, 2023)
Background: The prevalence data for postpartum depression globally reaches 10-15%. In Asia alone, the incidence of postpartum depression reaches 26 - 85%. Meanwhile in Indonesia, the incidence rate is 50-70%. Various interventions are carried out to reduce the prevalence of postpartum depression. Currently, many studies have found the effectiveness of reducing the risk of postpartum depression by preventing routine exercise during pregnancy.Objective: To discuss the effectiveness of exercise during pregnancy compared to the incidence of postpartum depression.Method: This paper involved on referral sources and based on observation by author.Results: Exercise is a non- pharmacological therapeutic effort that is able to reduce stressors in the body, increasing self-confidence inpregnant women who regularly exercise so as to reduce the risk of depression both during pregnancy and after pregnancy. Apart from being related to the mother's own physical factors, there are psychosocial factors that arise when a mother joins regular exercise classes during pregnancy. namely having a strong form of support among pregnant women so that they do not feel alone in facing physical and psychological changes during pregnancy, childbirth, and postpartum There are psychosocial factors that arise when a mother participates in routine exercise classes during pregnancy. namely having a strong form of support among pregnant women so that they do not feel alone in facing physical and psychological changes during pregnancy, childbirth, and postpartum.Conclusion: Psychosocial factors that arise when a mother participates in routine exercise classes during pregnancy having a strongform of support among pregnant women so that they do not feel alone in facing physical and psychological changes during pregnancy, childbirth, and postpartum. Keywords: prenatal, exercise, post-partum depression.